Correlation between resistin gene polymorphism and clinical aspects of lung cancer. Issue 52 (December 2017) - Hu, Wei-Wei; Tang, Chih-Hsin; Sun, Yi; Lu, Ting-Ting; Jiang, Pu; Wu, Yue-Ming; Wang, Chao-Qun; Yang, Shun-Fa; Su, Chen-Ming
Abstract : Abstract: Lung cancer is one of the most common cancers and is associated with a poor survival rate in the Chinese Han population. Analysis of genetic variants could lead to improvements in prognosis following lung cancer treatment. Resistin (RETN) is an important mediator of metabolic diseases and tumor progression. In this study, we explored the effects of RETN single nucleotide polymorphisms (SNPs) on the susceptibility and clinicopathological characteristics of patients with lung cancer. Four RETN SNPs (rs7408174, rs1862513, rs3745367, and rs3219175) were analyzed using TaqMan SNP genotyping in 371 patients with lung cancer and 451 cancer-free controls. The results showed that the RETN SNP rs3219175 with AG or at least 1 A allele was associated with a higher risk of lung cancer than wild-type (GG) carriers. Moreover, the RETN SNP rs3219175 with AG or AG + AA alleles was associated with a higher risk of distant metastasis than that in patients carrying GG alleles. We also used genotype-tissue expression datasets to compare the correlation of the RETN SNP rs3219175 in lung tissue and whole blood. In conclusion, our study demonstrated, for the first time, that RETN polymorphisms were correlated with lung cancer progression in the Chinese Han population.